Advanced biomaterials for diabetes healthcare and complication therapy: A review - Guoliang Wang; Weifang Liao; Feng Han; Yuying Shi; Zhijian Hu (APL Materials)
With the rapid increase in the number of patients with diabetes, exploring more effective and convenient methods to lower blood sugar levels is becoming increasingly important. Biomaterials are a potential solution in this field, owing to their unique customizability and biocompatibility. These materials can be used in smart drug delivery systems to achieve precise control of insulin release, or as islet cell encapsulation materials to achieve effective transplantation of islet cells. Among these, new responsive biomaterials can automatically adjust the release of insulin according to real-time changes in blood sugar levels, thereby enabling personalized and automated treatment. In addition, biomaterials are used to develop noninvasive blood glucose monitoring technologies to further simplify diabetes management. Although these applications are still in the research or early pilot stage, their potential to improve diabetes treatment and the quality of life of patients is already evident. In this Review, we discuss the current progress, limitations, and potential of biomaterials for the treatment of diabetes and its complications.